1998
DOI: 10.1056/nejm199811193392103
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Connexin 26 Gene (GJB2) among Ashkenazi Jews with Nonsyndromic Recessive Deafness

Abstract: The high frequency of carriers of mutations in GJB2 (4.76 percent) predicts a prevalence of 1 deaf person among 1765 people, which may account for the majority of cases of nonsyndromic recessive deafness in the Ashkenazi Jewish population. Conservation of the haplotype flanking the 167delT mutation suggests that this allele has a single origin, whereas the multiple haplotypes with the 30delG mutation suggest that this site is a hot spot for recurrent mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
375
3
15

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(407 citation statements)
references
References 21 publications
14
375
3
15
Order By: Relevance
“…14,15 As of June 2010, more than 200 different allelic variants in the GJB2 gene have been ascertained (http://www.hgmd.cf.ac.uk/ac/index.php). 16 The 167delT, 235delC, R143W and W24X mutations are the most common mutations in the Ashkenazi Jewish, 17 Japanese, 18 Ghanian 19,20 and Indian populations, 21,22 respectively (Figure 1). Thus, an ethnic-specific pattern is noted for some mutations of this gene, 16,21 which is different from that reported among various cohorts of Iran.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…14,15 As of June 2010, more than 200 different allelic variants in the GJB2 gene have been ascertained (http://www.hgmd.cf.ac.uk/ac/index.php). 16 The 167delT, 235delC, R143W and W24X mutations are the most common mutations in the Ashkenazi Jewish, 17 Japanese, 18 Ghanian 19,20 and Indian populations, 21,22 respectively (Figure 1). Thus, an ethnic-specific pattern is noted for some mutations of this gene, 16,21 which is different from that reported among various cohorts of Iran.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…It is an extremely heterogeneous disorder in which at least 30 reported loci [Van Camp et al, 1997;Zbar et al, 1998;Keats and Berlin, 1999] and mutations in one gene (GJB2) have been shown to be major cause of ARNSD in many different populations [Maw et al, 1995;Gasparini et al, 1997;Kelsell et al, 1997;Park et al, 2000;Morell et al, 1998;Zelante et al, 1997]. We have studied the mutation load of GJB2 in the Iranian population and have found the prevalence to be much lower than in other studied populations (Najmabadi et al, 2001; submitted manuscript).…”
Section: New Mutations; Rare and New Genesmentioning
confidence: 99%
“…In the Caucasian populations (European descendants), a single mutation, c.35delG, accounts for the majority of HL caused by GJB2 mutations, with a carrier frequency varying from 1 to 5% (Gasparini, et al, 2000). Among the Ashkenazi Jewish, in East Asians and in Africans, the predominant mutations are c.167delT, c.235delC mutation, and p.Arg143Trp, respectively (Brobby, et al, 1998;Kudo, et al, 2000;Morell, et al, 1998).…”
Section: Introductionmentioning
confidence: 99%